Carbon dioxide removal using calcium aluminate carbonates on titanic oxide under warm-gas conditions. (15th January 2016) - Yu, Ching-tsung; Kuo, Huan-ting; Chen, Yi-ming
Graphical abstract: Highlights: CO2 sorbents of Ca/Al/Ti x was prepared by precipitation-and-deposition method. Sorption CO2 was tested at 750 °C by TG analysis and fixed-bed reactor. CO2 capture stability was 96–98% after ten cycles at 750 °C by TG analysis. Scale-up production of Ca/Al/Ti x granule and their CO2 capture in reactor was tested. Abstract: This study presents a scale-up production method for Ti including Ca/Al sorbents and their CO2 sorption test under warm gas conditions by thermogravimetric (TG) analysis and fixed-bed reactor experiments. The Ca/Al/Ti x sorbents are made by the precipitation-and-deposition method where Ca 2+ and Al 3+ ions are deposited via an alkaline solution of OH − /CO3 2− on TiO2 powder. The titanium dioxide binder facilitates CO2 capture and enhances the CO2 capacity and multicycle stability by adjusting the Ti/Ca ratio. The results showed that these sorbents exhibited excellent CO2 capture stability of 96–98% after ten cycles at 750 °C by TG analysis. Characterization by XRD indicated that the reduction in the deterioration of the sorbent during the cycle test could possibly result from the formation of an anti-sintering compound such as CaTiO3 along with calcium aluminate hydroxides related to katoite. Using a reactor as test rig, the amount of sorbent and total capture weight was significantly increased. This TiO2 -coated sample of Ca/Al/O–TiO2 provides a feasible route for the manufacture of cheap CO2 sorbents.